2019
DOI: 10.4103/ijd.ijd_179_18
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary Study of the Effect of Semaphorin 3A and Acitretin on the Proliferation, Migration, and Apoptosis of HaCaT Cells

Abstract: Background: Vascular endothelial growth factor (VEGF) is significantly elevated in psoriatic patients and is associated with the severity of the psoriasis. Due to the effect of inhibiting production of VEGF, acitretin can effectively treat psoriasis. Semaphorin 3A (Sema3A) restrain tumor growth and angiogenesis by partially reversing VEGF effects on tumor. However, the role of Sema3A in the pathogenesis of psoriasis is unclear. Aims and Objectives: This study aimed to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 25 publications
0
1
0
Order By: Relevance
“…Further analysis using CMap revealed that acitretin, derived from etretinate through a structural transformation from an ester to an acid structure, promotes normal keratinization by inhibiting abnormal proliferation and differentiation of keratinocytes. Additionally, avasimibe has the ability to regulate VEGF and participate in microvascular formation, thereby exerting its therapeutic effects [ 44 ]. Bortezomib, a novel proteasome inhibitor, has been shown to possess anti-inflammatory effects by inhibiting the activation of NF-κB, effectively alleviating angiotensin II-induced hypertension and aortic remodeling [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further analysis using CMap revealed that acitretin, derived from etretinate through a structural transformation from an ester to an acid structure, promotes normal keratinization by inhibiting abnormal proliferation and differentiation of keratinocytes. Additionally, avasimibe has the ability to regulate VEGF and participate in microvascular formation, thereby exerting its therapeutic effects [ 44 ]. Bortezomib, a novel proteasome inhibitor, has been shown to possess anti-inflammatory effects by inhibiting the activation of NF-κB, effectively alleviating angiotensin II-induced hypertension and aortic remodeling [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sema3A competes with VEGF for binding to the NRP1/NRP2 coreceptors to inhibit the mitogenic effects of VEGF in endothelial cells, leading to apoptosis and inhibition of migration in breast cancer cell lines [15]. In hematopoietic and leukemic cells, Sema3A can also partially reverse the effects caused by VEGF [16]. The action of semaphorins is shown in Figure 1.…”
Section: Introductionmentioning
confidence: 99%